Usefulness of CT Scan and MRI for the Detection and Evaluation of Brain Tumors - D. Saraswathi; G. Srirama Murthy (Asian Journal of Medical Radiological Research, 2020)
Background: Intracranial tumors can arise from various locations in the brain parenchyma. Computed tomography scan (CT) and magnetic resonance imaging (MRI) are important modalities for diagnosis of intracranial tumors. The aim of the study is to study the usefulness of CT scan and MRI for the detection and evaluation of brain tumors. Subjects and Methods: This was a prospective cross sectional study comprising of 95 patients diagnosed with brain tumors clinically. CT scan was done in all the patients and MRI was done in 45 patients. Findings were correlated with histopathology. Results: In the present study, age group distribution included from 20 years to more than 50 years.In the present study males were predominant and the male to female ratio was 1.3:1. All the cases, (100%) presented with seizures, followed by headache, hemiparesis and vomiting. Conclusion: CT scan and MRI imaging modalities are of utmost importance in diagnosing brain tumors. Early diagnosis is important and the imaging guides the neurosurgeon regarding appropriate surgical approach.